The Effects of Emotional Intelligence on Organizational Citizenship Behavior and Unproductive Work Behavior - Saeed Yarmohammadi Monfared; Abbas Naghizadeh Baghi; Mehrdad Moharramzadeh; Parissa Khoeini (فرایند مدیریت و توسعه, 2022)
Purpose: This study aimes to investigate the effects of emotional intelligence on the occurrence of positive work behaviors such as organizational citizenship behavior and the reduction of destructive behaviors such as unproductive work behavior in the organization. Methodology: This research was of applied and survey type. The statistical population consisted of all 315 employees of the Sports and Youth Departments of Zanjan Province. Using the Morgan table, the sample size was determined to be 172 and finally, 160 completed standardized questionnaires were analyzed. Data analysis was performed through path analysis method and structural equation model, using the  Lisrel software.